Necessary Metatheory for the Critique of Sociological Theories - Hamid Masoudi; Ali Yousofi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Sociological theories are diverse and this science needs rethinking and critique. If so, far sociological critiques have not had a clear framework. Therefore, a specific method and framework are needed to critique sociological theories. The purpose of this article is to provide a suitable framework for criticizing theories. For this purpose, an attempt has been made to use a metatheoretical approach. The research method is documentary and review. Research findings show that the critique of sociological theories is necessary for theoretical progress in this field. But the critique process has significant challenges and metatheorizing is a good framework for overcoming these challenges. Metatheorizing allows for the rethinking and critique of theories and their deep understanding. Metatheorizing also creates a new theoretical perspective. In this research, six main steps for criticizing sociological theories are mentioned. These steps include identifying a theoretical problem or question, extracting the propositions and fundamental theorems of the theory, identifying and analyzing the assumptions of the theory, analyzing the compatibility of the theory, examining the connection of theory with other theories, examining the empirical validity of the theory, comparing theory with other theories, extracting similarities and differences, and theoretical links.